Improving quality of work life for care providers by fostering the emotional well-being of persons with dementia: a cluster-randomized trial of a nursing intervention in German long-term care settings - Berendonk, Charlotte; Kaspar, Roman; Bär, Marion; Hoben, Matthias (Dementia, 2019)
We tested the feasibility of a nursing intervention (DEMIAN) in routine care and its effects on care providers’ job satisfaction, motivation, and work strain., This cluster-randomized trial was conducted in 20 German long-term care facilities. We randomly assigned 20 facilities to an intervention group (84 care providers, 42 residents with dementia) or a control group (96 care providers, 42 residents with dementia). Intervention group providers received two training days on the intervention; 68 providers attended both training days. Sixty two providers completed both baseline and follow-up questionnaires., Trained providers created individualized mini-intervention plans for participating residents. Control group residents received ‘usual care’. Intervention group providers stated that the intervention was feasible and helped them improve emotional well-being of residents with dementia. We found significantly decreased time pressure and decreased job dissatisfaction for intervention group providers., DEMIAN is an effective and pragmatic contribution to implementing person-centred care in long-term care, with positive effects on providers’ working conditions.
First published March 17, 2017
Gesehen am 31.07.2019